Investigation of phase equilibria in the Ti-Co-Zr ternary system. (March 2017) - Zeng, Y.; Zhu, L.L.; Cai, G.M.; Liu, H.S.; Huang, J.W.; Jin, Z.P.
Abstract: Isothermal sections of the Ti-Co-Zr ternary system at 1073 K and 1173 K were determined using Ti-Co-Zr diffusion triples and equilibrated alloys with optical microscopy (OM), X-ray diffraction (XRD), scanning electron microscope (SEM) and electron probe micro-analysis (EPMA) techniques. A unknown ternary phase with composition of ～Ti31.3 Co37.9 Zr30.8 was observed to be stable at both 1073 K and 1173 K. Two continuous solid solutions Co2 (Ti, Zr) and Co(Ti, Zr) were formed between the binary intermediate compounds Co2 Ti (c) and Co2 Zr (c) as well as between the CoTi and CoZr intermediate compounds, respectively. The solubility of Zr in the CoTi2 phase was nearly 55.0 at% at both 1073 K and 1173 K, and the Co11 Zr2 phase was proved to be non-existent at 1073 K and 1173 K. Liquid phase was observed at 1173 K and exists with a wide range in the Ti-Zr-rich part. Highlights: Isothermal sections at 800 ℃ and 900 ℃ of Ti-Co-Zr system were determined. An unknown ternary phase μ was observed to be stable at both 800 °C and 900 °C. The solubility of Zr in CoTi2 phase was determined. The liquid phase exists with a wide range in the Ti-Zr-rich part at 900℃.